Penerapan Teknologi Irigasi Tetes Sederhana Berbasis Infus Botol Plastik untuk Efisiensi Air dan Optimalisasi Pekarangan di Desa Burai Ogan Ilir: Application of Simple Drip Irrigation Technology Based on Plastic Bottle Infusion for Water Efficiency and Yard Optimization in Burai Ogan Ilir Village - Puspitahati, Puspitahati; Triana, Arjuna Neni; Aulia, Nurul Izzah; Aditya, Bimo Brata; Iskandar, K. H. (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The community service program in Burai Village, Ogan Ilir, aims to improve water-use efficiency and optimize yard utilization by applying a simple drip irrigation system using plastic infusion bottles. This program was carried out over five months through several stages, including field surveys, dissemination of information about the drip irrigation system, assistance with installation in home gardens, and monitoring of water-use effectiveness. In addition, an evaluation was conducted to assess the community's level of understanding and skills after participating in the outreach activities. The results show that the drip irrigation technology using plastic infusion bottles can reduce water usage and provide more stable soil moisture for home-garden plants. Residents also understood the 3R concept (reduce, reuse, recycle) by using readily available plastic bottles from the surrounding environment. This outreach activity effectively increased residents' knowledge of water-saving irrigation techniques, enhanced awareness of using plastic waste as a simple technological medium, and encouraged community independence in developing productive home gardens. Overall, the program strengthened community capacity to apply environmentally friendly, appropriate, and sustainable technologies.